Laboratory Evaluation of Supernemic Insecticide (Neem Oil) and its Effect on Larvae of Big Headed myiasis Blow Fly Chrysomya Megacephala (Fibricius, 1794) (Diptera: Calliphoridae) - Nawal Sadiq Mehdi (Journal of Global Pharma Technology, 2018)
This study was carried out to evaluate the efficiency of Supernemic in the control of larvae of big headed myiasis fly Chrysomya megacephala by direct spraying and food treatment, the results of direct spraying of the second instar larvae with concentrations 0.3, 0.6 and 1ml.l-1 led to cumulative mortality reached 25, 37 and 59% respectively, with a decrease in the emergence number of adults insects to 75, 36 and 41%, respectively, as well as 76% of the adults which produced from larvae were treated with 1 ml.l-l of supernemic died after 24 hours, some of malformation in the dead larvae was noted such as blackening the whole body of the larva or appearance of black spots on it. The treatment of larval food with same concentrations showed a cumulative mortality reached 27, 64 and 65%, respectively, and the adults emergence percentage were 67, 36 and 35 respectively, we conclude that the larvae of this fly were sensitive to the insecticide, as well as food treatment was more efficient in controlling of this fly compared to the direct spraying treatment.Keywords: Neem oil, Myiasis, Chrysomya megacephala.